Correlation of Physical Activity with Physical Fitness and Posture in Female Adolescents - Lestari, Utami Sasmita; Angmalisang, Elvin Clara; Kurniawaty Wijaya, Nur Anindhita (Media Karya Kesehatan, 2026)
Physical activity is an essential factor in supporting physical health and posture, especially during adolescence, which is a critical period for physical and psychological development. This study aims to evaluate the relationship between physical activity levels and physical health and posture among adolescent girls. The study used a cross-sectional design with subjects aged 12–17 years attending MTS Assalam Manado. Physical activity was measured using a 2×24-hour recall method and categorized based on Physical Activity Level (PAL). Components of physical health assessed include nutritional status, somatotype, and posture. The results show a significant relationship between physical activity and nutritional status (p=0,001), somatotype (p=0,001), and posture (p=0,001). Adolescents with higher levels of physical activity tend to have better nutritional status, a more athletic somatotype, and a more normal posture. These findings emphasize the importance of structured physical activity in adolescents as a preventive strategy to maintain fitness and musculoskeletal health.Keywords: Adolescent girls, physical activity, physical health, posture somatotype, nutritional status.